Reciprocity with Canada. The Canadian Viewpoint - Paton, H. S. (Quarterly Journal of Economics, 1921)
The reciprocity agreement of 1911, 574. — Its rejection by Canada, 578. — Reciprocity and the Underwood tariff, 582. — Canadian tariff amendments, 1911–20, 582. — The trade between the two countries, 1910–20, 585. — The present status of reciprocity in Canada, 588. — Conclusions, 591.